Workshop Kesiapan Karir Akuntan Vokasi Menjawab Tantangan dan Meraih Peluang di Era Artificial Intelligence: Pengabdian - Fajrillah; Sudarso, Andriasan; Almastoni; Angela Anastasya Zagoto; Nelisa Aulia br Ginting; Della Puspita Br Pangaribuan (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service program aimed to enhance the career readiness of Vocational High School (SMK) Accounting students in facing the disruption of Artificial Intelligence (AI) technology. The method used was an interactive workshop comprising material presentation, discussion, case studies, and Student Worksheets (LKS). The activity was carried out at SMK Swasta IRA Medan, with participants consisting of teachers and students from the Accounting department. Evaluation results through LKS and Q&A sessions indicated an increase in participants' understanding of the role of AI in accounting, as well as awareness of the importance of mastering hard skills such as accounting software and data literacy, and soft skills such as critical thinking, communication, and adaptability. It was concluded that this workshop successfully equipped participants with new perspectives and strategies to answer challenges and seize opportunities in the AI era. SMK Accounting graduates are encouraged to shift from the role of data entry to data supervisors and junior analysts.